ENTREPRENEURSHIP INTERESTS AMONG STUDENTS OF CIPUTRA COLLEGE OF ECONOMICS MAKASSAR - Andrean Kevin; A. Sutradea Zalsabila; Devi Triana Coanda; Justin Wijaya; Tony Antonio (Accounting Profession Journal (APAJI))
The objectives of this study are: (1) To increase students' interest in entrepreneurship. (2) To motivate students to become entrepreneurs and familiarize them with their creative abilities to make business plans and encourage young entrepreneurship. (3) To overcome the decline, increasing student entrepreneurship is very important. (4) One way to increase Indonesia's economic growth is to develop young entrepreneurs. Although many graduates are born in Indonesia every year, there are still many students who are not interested in becoming entrepreneurs. This quantitative research uses primary data (objects, samples, questionnaires, and analysis tools); (1) Distributing questionnaires via the internet and collecting basic data based on respondents' responses; (2) Processing and analyzing data; holding focus group discussions (FGD) on research findings; and (3) Making a final research report.